Increasing the collaboration’s effectiveness in networked online groups by the using of competency-based workflow - Slavin, Alexander; Slavin, Boris (International Journal of Engineering and Technology, 2018)
The article is devoted to the investigation of the possibility of increasing the effectiveness of the collaboration of experts using network tools for communication during general expert work. It is shown that the use of standard network tools simulating a "common room" on the Internet makes the communication of experts chaotic and uneven. Other situation arises, if in network communication to include workflow elements, when each expert will have his own task, there will be his partners. At the same time, tasks should be based on the competence of experts, related both to their knowledge and their ability to perform analytical or creative functions. In this case, communication becomes more homogeneous, and the effectiveness of general tasks to be solved is higher.Â